GCMMF: Preempting Competition with an Innovative Business Model - Parekh, Mohit Avinashkumar (Indian Journal of Marketing, 2011)
Globalization has made market place highly competitive for companies. The fast paced changes in consumer preferences and technology are constantly baffling the long time successful companies. These changes provide an opportunity for any new company to enter the market place and challenge the leaders. But there are companies who are trying to change themselves before they are forced to change by their competitors. This article is about one such Indian FMCG company, which is constantly endeavouring to change the rules of the industry in future. The company is using an innovative, never used before, business model to change their retailing strategy and pre-empt the future competition and retain its leadership position in the future.